Near-Field Ultrasound Imaging During Radiofrequency Catheter Ablation: Tissue Thickness and Epicardial Wall Visualization and Assessment of Radiofrequency Ablation Lesion Formation and Depth. (December 2017) - Haines, David E.; Wright, Matthew; Harks, Erik; Deladi, Szabolcs; Fokkenrood, Steven; Brink, Rob; Belt, Harm; Kolen, Alexander F.; Mihajlovic, Nenad; Zuo, Fei; Rankin, Darrell; Stoffregen, William; et al.
Abstract : Background: Safe and successful radiofrequency catheter ablation depends on creation of transmural lesions without collateral injury to contiguous structures. Near-field ultrasound (NFUS) imaging through transducers in the tip of an ablation catheter may provide important information about catheter contact, wall thickness, and ablation lesion formation. Methods and Results: NFUS imaging was performed using a specially designed open-irrigated radiofrequency ablation catheter incorporating 4 ultrasound transducers. Tissue/phantom thickness was measured in vitro with varying contact angles. In vivo testing was performed in 19 dogs with NFUS catheters positioned in 4 chambers. Wall thickness measurements were made at 222 sites (excluding the left ventricle) and compared with measurements from intracardiac echocardiography. Imaging was used to identify the epicardium with saline infusion into the pericardial space at 39 sites. In vitro, the measured exceeded actual tissue/phantom thickness by 13% to 20%. In vivo, NFUS reliably visualized electrode-tissue contact, but sensitivity of epicardial imaging was 92%. The chamber wall thickness measured by NFUS correlated well with intracardiac echocardiography ( r =0.86; P <0.0001). Sensitivity of lesion identification by NFUS was 94% for atrial and 95% for ventricular ablations. NFUS was the best parameter to predict lesion depth in right and left ventricle ( r =0.47; P <0.0001; multiple regression P =0.0025). Lesion transmurality was correctly identified in 87% of atrial lesions. Conclusions: NFUS catheter imaging reliably assesses electrode-tissue contact and wall thickness. Its use during radiofrequency catheter ablation may allow the operator to assess the depth of ablation required for transmural lesion formation to optimize power delivery. Abstract : Supplemental Digital Content is available in the text.